Strengths and Weaknesses of Cognitive Theory - Mana Alahmad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This paper focuses on strengths and weaknesses of the Cognitive Theory. Many theories have been proposed over the years to explain the developmental changes that people undergo over the course of their lives. These theories differ in the conceptions of human nature they adopt and in what they regard to be the basic causes and mechanisms of human motivation and behavior. Piaget's theory of cognitive development explains how a child constructs a mental model of the world. He disagreed with the idea that intelligence was a fixed trait, and regarded cognitive development as a process which occurs due to biological maturation and interaction with the environment. Cognitive learning theory is best used to guide learning when trying to build usefulness Knowledge structures, and clinical reasoning teaching. The theory suggests that Clinical exercise is crucial to the organization of Memory Knowledge and Recall Facilitation. This means teachers will be expected to be aware of prior clinical experiences of the learner before assessing the learner’s experience Powerful performance.